Evidence-Based Research in STEM Teacher Education: From Theory to Practice - Milner-Bolotin, Marina (Frontiers in Education, 2018)
The paper identifies possible causes of STEM education reform failures and suggests how repairing the link between evidence-based education research and teacher education practice may address the problem. The evidence-based STEM education research is described and placed in the STEM teacher education context. The paper shows how this research may help reverse the growing student STEM disengagement, support effective learning environments, bring attention to teacher professional development, and inform STEM education policy. The paper calls on placing research-based STEM teacher education in the center of contemporary reform efforts and conducting evidence-based education research to study the effect of this process on the growth of teacher knowledge and subsequently on student learning. The major claim is that research-based teacher education and professional development are key factors in successful implementation of STEM education reforms. However, more research is needed to examine this assertion. We suggest a four-step approach for incorporating evidence-based education research and teacher education practice as a potential solution: Model-Reflect-Research-Practice. This approach emphasizes teacher-candidates' active engagement with research-based pedagogies as learners and as future teachers. It provides a universal framework for incorporating research-based pedagogies in teacher education as described in the two examples. The first example showcases Peer Instruction supported by PeerWise technology used to promote conceptual understanding through peer learning. The second example focuses on supporting teacher-candidates' growth by asking them to teach short mini-lessons, record and upload them onto the online collaborative platform (Collaborative Learning Annotation System) for peer feedback and reflection. Both examples incorporate collaborative educational technologies to promote the development of teacher-candidates' knowledge for STEM teaching and their growth mindset. The paper emphasizes how making evidence-based STEM education research a foundation of teacher education can help connect education research to teacher education practice and break the vicious circle of STEM education reform failures.